Duelling identities in refugees learning through open, online higher education - James Brunton; Orna Farrell; Eamon Costello; Lorraine Delaney; Colum Foley; Mark Brown (Open Praxis, 2019)
This paper reports on a qualitative study of the transition experiences of refugees studying through open and online higher education. Online, open education programmes have considerable potential to provide flexible access to education for refugees, who are not well represented within higher education. As part of a wider University of Sanctuary initiative, interview data from six Ireland-based refugees was analysed using a data-led, qualitative methodological framework grounded in discursive psychology. Findings indicate that participants’ transition narratives are typical in many ways as they form student identities while managing their existing identities and begin to feel, or not, that they belong. Participants constructed a stark divide between two duelling identities, between their identity as a refugee and their new identity as an online learner. Identification with the university was emphasised in contrast to disidentification with the ‘asylum world’. These findings indicate that a strategically connected approach to supporting refugees transition into higher education can impact positively on these students.